Vitamin D Levels and Disease Activity in Children with Systemic Lupus Erythematosus - Elif ÇOMAK; Sema AKMAN; Çağla Serpil DOĞAN; Mustafa KOYUN; Arife USLU GÖKÇEOĞLU; Sabahat ÖZDEM2 (Archives of Rheumatology, 2014)
Objectives: This study aims to evaluate the association between vitamin D deficiency and disease activity in children with juvenile systemic lupus erythematosus (SLE). Patients and methods: A total of 16 children (13 girls and 3 boys; mean age 14.47 years; range 5-18) with SLE who were under followup in our clinic were included in this study. The medical records of the children along with the demographic data, disease duration, treatments received, disease activity, and 25-hydroxyvitamin D [25-(OH)D] levels were evaluated. Systemic lupus erythematosus disease activity (SLEDAI) scores were calculated on the day the serum samples were drawn. Results: The median follow-up period was 30 (range 9 to 55) months. The mean serum vitamin D level was 22.04±16.75 ng/ml. Vitamin D deficiency (serum vitamin D level of <15 ng/ml) was found in half of the patients. Six of them had significantly lower vitamin D levels (≤10 ng/ml). A significant negative correlation between the serum concentrations of vitamin D and the SLEDAI scores was found (r= -0.711, p=0.002). Conclusion: Our study results show that there is a strong negative association between disease activity and vitamin D deficiency in children with SLE. The vitamin D levels of these patients should be evaluated on a regular basis, and vitamin D supplements should be given, if necessary.